Prevalence of fecal carriage of vancomycin resistant Enterococci in a tertiary care centre in South India - Murugesan, Vinitha; Gounassegarane, Dhanalakshmi; Karanam, Gnanaprakash; Jayarajan, Jayalakshmi (International Journal of Research in Medical Sciences, 2025)
Background: The number of VRE infections gradually increases worldwide and ICUs in hospitals which remains to be the major reservoir of antibiotic-resistant organisms. The current study was carried out to determine prevalence of fecal carriers of vancomycin resistant Enterococci in a tertiary care hospital, thereby preventing the spread of vancomycin resistant Enterococci to patients under high risk. Methods: A total of 219 stool samples and rectal swabs were collected from health care workers and ICU patients and processed in vancomycin resistant Enterococci agar and subjected to certain phenotypic tests for its species identification. Antimicrobial susceptibility testing was done for all the vancomycin resistant enterococcal isolates. Results: A total of 73 VRE were isolated of which 64 (36%) were from HCW and 9 (22%) were from ICU patients. The prevalence of VRE was 33% and the most common VRE isolated was Enterococcus faecium. All the 73 VRE isolates were susceptible to linezolid and 52% were susceptible to quinpristine/dalfopristine. Conclusions: Screening of stool samples aids in the prevention of spread of multi-drug resistant VRE isolate from HCW to high risk patients. It’s imperative to step up infection control strategies so as to curtail its spread.